Naturally Occurring Disk Herniation in Dogs: An Opportunity for Pre-Clinical Spinal Cord Injury Research - Levine, Jonathan M. (Mary Ann Liebert, Inc., 2011)
Traumatic spinal cord injuries represent a significant source of morbidity in humans. Despite decades of research using experimental models of spinal cord injury to identify candidate therapeutics, there has been only limited progress toward translating beneficial findings to human spinal cord injury. Thoracolumbar intervertebral disk herniation is a naturally occurring disease that affects dogs and results in compressive/contusive spinal cord injury. Here we discuss aspects of this disease that are analogous to human spinal cord injury, including injury mechanisms, pathology, and metrics for determining outcomes. We address both the strengths and weaknesses of conducting pre-clinical research in these dogs, and include a review of studies that have utilized these animals to assess efficacy of candidate therapeutics. Finally, we consider a two-species approach to pre-clinical data acquisition, beginning with a reproducible model of spinal cord injury in the rodent as a tool for discovery with validation in pet dogs with intervertebral disk herniation.